The Hyperglycemic Effect of Different Particle Sizes of Composite Flour from Maize, Wheat and African Breadfruit on Adult Diabetic Albino Rats - Okakpu, Chidiebere; Okakpu, KG; Ubbor, SC (PUI BiGME Universitas Jambi, 2024)
This study was carried out to determine the hyperglycemic effect of diets prepared with different particle sizes of composite flour from Maize (Zea mays), Wheat (Triticum aestivum) and African breadfruit (Treculia africana) on adult diabetic albino rats (Rattus norvegcus). The samples were milled into different particle flour sizes and used to prepare three different sets of diets (diet A, diet B, and diet C). Diet A represents the fine particle size composite flour, diet B represents medium particle size composite flour, while diet C represents coarse particle size composite flour. The broiler finisher, which serves as the control represents diet D. Sixteen rats were used in this experiment and separated into four groups of four rats each (three experimental groups and one control group). The experimental groups were injected with alloxan to induce diabetes, while the control group was injected with saline solution. Groups 1, 2, 3 and 4 were fed with diets A, B, C and D respectively and their fasting blood glucose level were determined at intervals for a period of twenty-one days. Group 3 had the lowest blood glucose level range (80 to 100 mg/dL) more than diets A and B which has blood glucose level range of 82 to 109 mg/dL and 103 to 124 mg/dL respectively. This is an indication that the particle size of diet C is the best in the management of diabetes among the other diets. Therefore, the particle size of diet C is more effective in the management of diabetes than that of diets A and B. However, the three diets were able to reduce the blood glucose level to normal.